Freedom of language choice in civil proceeding of the Republic of Kazakhstan – as a constitutional principle (Journal of actual problems of jurisprudence, 2018)
In this article is considered to freedom of elective language in the civil courts process, as to as is constitutional law principals. The principle of a freedom of choice of language in civil legal proceedings in the Republic of Kazakhstan is generally considered in two aspects. On the one hand, this principle can be considered as the constitutional principle, on the other hand as the basic principle of a civil procedural law. The language choice in civil process as the constitutional principle is an integral part of the rights and freedoms of the person. Therefore, it is impossible to consider this principle only within a civil procedural law.Key words: civil legal proceedings, language of legal proceedings, constitutional principle, state language.